The Perception of Society Towards Divorce - Usman, M. (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This study took place in Bantul district since there were many divorce cases in this area, particularly more cases of divorce by litigation compared to those by thalaq every year. Moreover, it had the highest cases in the Special Region of Yogyakarta. According to data from the office of Ministry of Religious Affairs in Bantul, in 2013 the number of divorce by thalaq was recorded 194 cases, while the number of divorce by litigation was 456 cases. In 2014 the number of divorce by thalaq was 186 cases while the number of divorce by litigation was 553 cases. In 2015, there were 55 cases of divorce by thalaq and 198 cases of divorce by litigation. This study aimed at finding out the factors contributing to the high number in cases of divorce by litigation and exploring the perceptions of societies in Bantul towards divorce. This study used qualitative methods, so then data was collected from documents from Bantul Religious Court and Bantul Ministry of Religion, and interviews with women filling for divorce, religious leaders, and public figures. The findings of the study indicated that the factors causing the high number in divorce by litigation were economic factors, level of education, consumptive lifestyles, and changes in societies’ perceptions towards divorce. In addition, societies of Bantul regency believed that divorce was a common issue and considered as the best solution in solving family problems.